(untitled) (Tintas. Quaderni di Letterature iberiche e iberoamericane, 2012)
Recorrido bio-bibliográfico sobre la obra de la autora catalana Mercè Rodoreda (1908-1983). Bio-bibliographical survey on the works of the Catalan writer Mercè Rodoreda (1908-1983).